Messages of Nationalism and the Motivation to Return to Indonesia: A Critical Discourse Analysis of Sri Mulyani Indrawati's Lectures to LPDP Awardees - Akhmad Mukhibun; Andayani; Raheni Suhita; Ahimsa W Swadeshi; Khusnul Fatonah; Alifah Raihan Nur Hasanah (UIN Raden Mas Said Surakarta, Indonesia, 2026)
A speech or lecture plays a role in influencing one's perceptions, internalising values, and persuading people's will. This study aims to explore the textual and societal analysis that underpin the discourse of Sri Mulyani Indrawati's lectures during the Departure Preparation for LPDP scholarship awardees. This research used Teun A. Van Dijk's critical discourse analysis approach. The data sources used are two videos of Sri Mulyani Indrawati’s lectures on the YouTube channel of LPDP RI and news searches in the mass media. The results of this study are as follows. First, the macrostructure in the lectures is the theme